TECHNOLOGY ADAPTABILITY AS A MODERATING VARIABLE OF THE INFLUENCE OF DIGITAL COMPETENCE ON WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Metehsa Sembiring; Rabith Madah Khulaili Harsya; Debiyanti Kune; Dwi Anna Kristanti; Nuralam (JURNAL ILMIAH EDUNOMIKA, 2026)
In the rapidly evolving landscape of the fourth industrial revolution, the interplay between human capability and technological integration has become the primary determinant of organizational success. This study investigates the impact of digital competence on employee performance, with a specific focus on the mediating role of work motivation and the moderating effect of technology adaptability. As organizations transition toward fully digitized workflows, the mere possession of digital skills may no longer suffice to guarantee high performance; instead, the psychological drive and the fluid ability to adapt to new technological tools play a crucial role. Utilizing a quantitative approach with Structural Equation Modeling (SEM), this research analyzes data from professional employees across various sectors. The results indicate that digital competence significantly enhances work motivation, which in turn acts as a robust predictor of employee performance. Furthermore, the findings reveal that technology adaptability significantly moderates the relationship, suggesting that employees who are more agile in embracing new technologies derive higher motivational benefits from their digital skills. This study provides a comprehensive framework for Human Resource Management (MSDM) to design training programs that balance technical proficiency with psychological resilience and adaptability in the digital era.